Pengaruh Akuntabilitas, Transparansi, Partisipasi Masyarakat dan Kompetensi Aparatur Desa Terhadap Efektivitas Pengelolaan Dana Desa - Ilham Alfa Fauzan; Djoko Kristianto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of accountability, transparency, community participation, and village apparatus competence on the effectiveness of village fund management in Sidodadi Village, Masaran District, Sragen Regency. This research employed a quantitative approach using questionnaires as the data collection instrument. The population in this study consisted of the residents of Sidodadi Village, with a total sample of 85 respondents determined through a sampling method. Data were analyzed using validity tests, reliability tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The results indicate that accountability, transparency, community participation, and village apparatus competence have a positive and significant effect on the effectiveness of village fund management. Simultaneously, the four independent variables contribute 64% to the effectiveness of village fund management, while the remaining percentage is influenced by other factors not included in this study